Preparation method and application of lithium manganese iron phosphate

By using three-layer carbon coating technology in the preparation process of lithium manganese iron phosphate, the conductivity of the material is improved, the problem of low electronic conductivity is solved, and a wider range of lithium-ion battery applications are achieved.

CN119503756APending Publication Date: 2025-02-25HENAN LONGBAI NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411713047.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Lithium manganese phosphate has a low electronic conductivity, only 10-13S/cm, hindering its practical application in lithium-ion batteries.

Method used

The three-layer carbon coating technology is adopted to play a reducing agent in the first sand mill through the first composite carbon source, and the second composite carbon source is re-coated in the second sand mill, combining a reducing atmosphere and high-temperature calcination to enhance the graphitization degree of carbon substances, thereby improving the conductivity of lithium manganese iron phosphate.

Benefits of technology

It significantly reduces the internal resistance of lithium manganese iron phosphate, improves its conductivity, and expands its application range in lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503756A_ABST
    Figure CN119503756A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery positive electrode materials, in particular to a preparation method and application of lithium manganese iron phosphate. The preparation method of the lithium manganese iron phosphate comprises the following steps: (a) carrying out first sanding and first drying on a mixed solution containing an iron source, a manganese source, a lithium source, a phosphorus source and a first composite carbon source to obtain a dried material; (b) carrying out first sintering on the dried material in a composite atmosphere to obtain a sintered material; and (c) carrying out second sanding, second drying and second sintering on a mixed solution containing the sintered material and a second composite carbon source. According to the preparation method of the lithium manganese iron phosphate, the conductivity of the lithium manganese iron phosphate can be improved, the internal resistance of the lithium manganese iron phosphate is reduced, and the performance of the lithium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a preparation method of lithium manganese iron phosphate and application thereof. Background Art

[0002] With the further development of new energy electric vehicles, the market has put forward an urgent demand for high energy density lithium-ion batteries. When the energy density of lithium iron phosphate has almost reached its limit, lithium iron manganese phosphate has been discovered and favored by the market as its replacement product. Lithium manganese phosphate has the advantages of high safety, long cycle life, low cost and green environmental protection of lithium iron phosphate. It also has a dual voltage platform and can provide higher energy density for batteries. It is the focus of the future development of the positive electrode material market.

[0003] Although lithium manganese iron phosphate has a higher theoretical energy density than lithium iron phosphate, its electronic conductivity is lower than that of lithium iron phosphate, only 10 -13 S / cm, which greatly hinders its practical application.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing lithium manganese iron phosphate and its application. The method for preparing lithium manganese iron phosphate can prepare lithium manganese iron phosphate with low internal resistance, high conductivity and wide practical application range.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0007] One aspect of the present invention relates to a method for preparing lithium manganese iron phosphate, comprising the following steps:

[0008] (a) subjecting a mixed solution containing an iron source, a manganese source, a lithium source, a phosphorus source and a first composite carbon source to a first sand milling and a first drying to obtain a dried material;

[0009] (b) subjecting the dried material to a first sintering in a composite atmosphere to obtain a sintered material;

[0010] (c) subjecting the mixed solution containing the sintering material and the second composite carbon source to a second sand milling, a second drying and a second sintering.

[0011] The method for preparing lithium manganese iron phosphate can improve the conductivity of lithium manganese iron phosphate, reduce the internal resistance of lithium manganese iron phosphate, and improve the performance of lithium batteries.

[0012] Another aspect of the present invention also relates to a positive electrode plate, which is mainly made of lithium manganese iron phosphate prepared by the lithium manganese iron phosphate preparation method.

[0013] Another aspect of the present invention also relates to a secondary battery, comprising the positive electrode plate.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] The preparation method of lithium iron manganese phosphate provided by the present invention is based on the secondary sintering process of lithium iron manganese phosphate, and adopts a three-layer carbon coating technology. The first composite carbon source introduced in the first sand milling plays the role of a reducing agent, and after combustion, the iron source and the manganese source complete the valence change, and form carbon to wrap on the surface of the material; the reducing atmosphere introduced in the first sintering process plays the role of a reducing agent supplement, which can further promote the valence change of the iron source and the manganese source on the one hand, and can form a carbon material to coat the surface of the material on the other hand; the second composite carbon source introduced in the secondary sand milling process can be coated after the material is fully crushed; after high-temperature calcination again, the graphitization degree of the carbon material is improved, which can further improve the conductivity of the material. The three-layer carbon coating technology is adopted to reduce the internal resistance of lithium iron manganese phosphate and improve the conductivity of lithium iron manganese phosphate. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 The XRD spectrum of lithium iron manganese phosphate provided in the embodiment of the present invention;

[0018] Figure 2 The SEM result image of lithium manganese iron phosphate provided in the embodiment of the present invention;

[0019] Figure 3 This is a diagram of electrical performance test results provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0020] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0021] One aspect of the present invention relates to a method for preparing lithium manganese iron phosphate, comprising the following steps:

[0022] (a) subjecting a mixed solution containing an iron source, a manganese source, a lithium source, a phosphorus source and a first composite carbon source to a first sand milling and a first drying to obtain a dried material;

[0023] (b) performing a first sintering on the dried material under a composite atmosphere to obtain a sintered material;

[0024] (c) subjecting the mixed solution containing the sintering material and the second composite carbon source to a second sand milling, a second drying and a second sintering.

[0025] The preparation method of lithium iron manganese phosphate is based on the secondary sintering process of lithium iron manganese phosphate and adopts three-layer carbon coating technology. The first composite carbon source introduced in the first sand milling plays the role of a reducing agent. After combustion, the iron source and the manganese source complete the valence change and form carbon to wrap on the surface of the material; the reducing atmosphere introduced in the first sintering process plays the role of a reducing agent supplement, which can further promote the valence change of the iron source and the manganese source on the one hand, and can form carbon materials to coat the surface of the material on the other hand; the second composite carbon source introduced in the secondary sand milling process can be coated after the material is fully crushed; after high-temperature calcination again, the graphitization degree of the carbon material is improved, which can further improve the conductivity of the material. The three-layer carbon coating technology reduces the internal resistance of lithium iron manganese phosphate and improves the conductivity of lithium iron manganese phosphate.

[0026] Furthermore, the first composite carbon source includes: a first carbon source and a second carbon source.

[0027] Furthermore, the first carbon source includes at least one of glucose, fructose, galactose, sucrose or maltose.

[0028] Furthermore, the second carbon source includes at least one of polyethylene glycol, polyvinyl pyrrolidone, ascorbic acid or citric acid.

[0029] In order to improve the conductivity of lithium manganese iron phosphate and reduce its internal resistance, the present invention improves and adjusts the specific type of the first composite carbon source, and selects a specific type of the first carbon source and the second carbon source to form the first composite carbon source.

[0030] Furthermore, the mass of the first carbon source is 3% to 10% of the total mass of the iron source, the manganese source, the lithium source and the phosphorus source, including but not limited to any one of 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% or a range between any two of them.

[0031] Furthermore, the mass of the second carbon source is 2% to 8% of the total mass of the iron source, the manganese source, the lithium source and the phosphorus source, including but not limited to any one of 2%, 3%, 4%, 5%, 6%, 7% or 8% or a range between any two of them.

[0032] By limiting the addition amount of the first carbon source and the second carbon source, the addition amount of the first composite carbon source is further determined. The first carbon source and the second carbon source are added in a certain ratio, which can improve the conductivity of lithium manganese iron phosphate.

[0033] The present invention does not specifically limit the type of iron source, and any conventional iron source in the art can be used to implement the technical solution of the present invention. In some specific embodiments, the iron source includes, but is not limited to, at least one of anhydrous ferric phosphate, dihydrate ferric phosphate, red iron oxide, yellow iron oxide, or black iron oxide.

[0034] The present invention does not specifically limit the type of manganese source, and any conventional manganese source in the art can be used to implement the technical solution of the present invention. In some specific embodiments, the manganese source includes but is not limited to at least one of manganese dioxide, manganese tetraoxide, manganese carbonate or manganese phosphate.

[0035] The present invention does not specifically limit the type of lithium source, and any conventional lithium source in the art can be used to implement the technical solution of the present invention. In some specific embodiments, the lithium source includes but is not limited to at least one of lithium carbonate, lithium hydroxide, lithium phosphate or lithium dihydrogen phosphate.

[0036] The present invention does not specifically limit the type of phosphorus source, and any conventional phosphorus source in the art can be used to implement the technical solution of the present invention. In some specific embodiments, the phosphorus source includes but is not limited to at least one of monoammonium phosphate, diammonium hydrogen phosphate, lithium phosphate, iron phosphate or manganese phosphate.

[0037] Furthermore, the molar ratio of the iron source, the manganese source, the lithium source and the phosphorus source is (0.2-0.8):(0.8-0.2):(1.00-1.10):(0.98-1.15). The iron source, manganese source, lithium source and phosphorus source can be added according to the chemical formula of lithium iron manganese phosphate.

[0038] Furthermore, the composite atmosphere includes: an inert atmosphere and a reducing atmosphere.

[0039] Furthermore, the inert atmosphere includes but is not limited to: at least one of nitrogen, argon or helium.

[0040] Furthermore, the reducing atmosphere includes but is not limited to at least one of methane, ethane, acetylene or propane.

[0041] The first sintering is carried out in a composite atmosphere. In addition to the conventional protective atmosphere, a reducing gas is also added to the composite atmosphere. The reducing atmosphere plays the role of a reducing agent supplement, which can further promote the valence change of the iron source and manganese source, and can also form carbon materials to coat the surface of the material, further improving the conductivity of lithium manganese iron phosphate and reducing the internal resistance.

[0042] Furthermore, the reducing atmosphere content does not exceed 2% of the total volume of the composite atmosphere, including but not limited to any one of 0.01%, 0.05%, 0.1%, 0.15% or 2% or any range between two values. Within the limited sintering time, it is necessary to ensure that a sufficient amount of reducing atmosphere is introduced to participate in the reaction and form a sufficient amount of carbon material on the surface of lithium manganese iron phosphate.

[0043] Furthermore, the temperature of the first sintering is 450-600°C, including but not limited to any one of 450°C, 480°C, 500°C, 530°C, 550°C, 580°C or 600°C or any range between two thereof. The first low-temperature sintering mainly acts to activate the lithium source and nucleate the grains. Below this temperature range, the lithium source is difficult to be effectively activated, and above this temperature range, the grains will grow rapidly, affecting the electrical properties of the final product.

[0044] Furthermore, the first sintering time is 4 to 8 hours, including but not limited to any one of 4 hours, 5 hours, 6 hours, 7 hours or 8 hours or a range between any two of them.

[0045] Furthermore, the second composite carbon source includes: a third carbon source and a fourth carbon source.

[0046] Furthermore, the third carbon source includes, but is not limited to, at least one of polyethylene glycol, polyvinyl pyrrolidone, ascorbic acid or citric acid.

[0047] Furthermore, the fourth carbon source includes but is not limited to at least one of Super P, acetylene black, Ketjen black, graphene oxide or carbon nanotubes.

[0048] In order to reduce the internal resistance of lithium manganese iron phosphate, the present invention improves and adjusts the specific type of the second composite carbon source, and selects a specific type of third carbon source and fourth carbon source to form the second composite carbon source.

[0049] Furthermore, the mass of the third carbon source is 0.5% to 3% of the mass of the sintering material, including but not limited to any point value of 0.5%, 1%, 1.5%, 2%, 2.5% or 3% or a range value between any two of them.

[0050] Furthermore, the mass of the fourth carbon source is 0.2% to 1% of the mass of the sintering material, including but not limited to any point value of 0.2%, 0.4%, 0.6%, 0.8% or 1% or a range value between any two of them.

[0051] By limiting the addition amount of the third carbon source and the fourth carbon source, the addition amount of the second composite carbon source is further determined. The third carbon source and the fourth carbon source are added in a certain ratio, which can improve the conductivity of lithium manganese iron phosphate.

[0052] Further, the temperature of the second sintering is 700-800°C, including but not limited to any point value of 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C or 800°C or any range value between two of them. The general synthesis temperature range of lithium manganese iron phosphate mainly occurs in this temperature range. The main function of the second sintering is to promote particle growth, improve the degree of crystallization, optimize the orderliness of the atomic arrangement of the material, and stabilize the crystal structure.

[0053] Furthermore, the second sintering time is 2 to 6 hours, including but not limited to any one of 2 hours, 3 hours, 4 hours, 5 hours or 6 hours or a range between any two of them.

[0054] Furthermore, the second sintering is performed under a protective atmosphere.

[0055] Furthermore, the second sintering further includes: crushing.

[0056] In some specific embodiments, the crushing methods include but are not limited to: mechanical crushing or air flow crushing.

[0057] When preparing the mixed solution of the present invention, the solvent used includes but is not limited to: deionized water.

[0058] The sand grinding involved in the present invention is carried out in a sand grinder.

[0059] The drying method involved in the present invention can be any conventional drying method in the art. In some specific embodiments, the drying method includes but is not limited to at least one of spray drying, flash drying or oven drying.

[0060] Another aspect of the present invention also relates to a positive electrode plate, which is mainly made of lithium manganese iron phosphate prepared by the lithium manganese iron phosphate preparation method.

[0061] Another aspect of the present invention also relates to a secondary battery, comprising the positive electrode plate.

[0062] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0063] Example 1

[0064] The method for preparing lithium manganese iron phosphate provided in this embodiment comprises the following steps:

[0065] (1) 751.9 g of manganese dioxide, 2000 g of iron phosphate, 1015.2 g of monoammonium phosphate, 824.8 g of lithium carbonate, 355.1 g of sucrose, and 120.5 g of polyethylene glycol were weighed, mixed in 8 kg of pure water, and placed in a sand mill for thorough sand grinding. The sand-milled slurry was spray-dried to obtain a dry material 1;

[0066] (2) placing the dried material 1 obtained in step (1) in a box-type atmosphere furnace, and sintering at 500° C. for 5 h in a mixed atmosphere of circulating nitrogen (99%) and ethane (1%) to obtain a sintered material 1;

[0067] (3) Weigh 2000 g of the sintered material 1 obtained in step (2), add 10 g of polyethylene glycol and 10 g of acetylene black, mix in 4 kg of pure water, and place in a sand mill for thorough sand grinding. Spray dry the sand milled slurry to obtain a dried material 2;

[0068] (4) The dried material 2 obtained in step (3) is placed in a box-type atmosphere furnace, and sintered at 740° C. for 4 h in a circulating nitrogen atmosphere to obtain a sintered material 2, which is then mechanically crushed to obtain lithium manganese iron phosphate.

[0069] Samples were taken for XRD, SEM and electrical performance tests. The results are as follows: Figure 1 , Figure 2 , Figure 3 As shown. The XRD spectrum shows that the diffraction peak of the synthesized material corresponds to the standard card representing lithium manganese iron phosphate (JCPDS#01-073-7355), without impurity phase. SEM shows that the primary particles of the lithium manganese iron phosphate material are spherical in morphology, and there is a flocculent structure of carbon deposition on the surface. The electrical performance test results show that the material has an obvious dual voltage platform, the first charge specific capacity reaches 161.4mAh / g, and the discharge specific capacity is 153.0mAh / g.

[0070] Example 2

[0071] The method for preparing lithium manganese iron phosphate provided in this embodiment comprises the following steps:

[0072] (1) 686.2 g of manganese dioxide, 1058.3 g of diammonium hydrogen phosphate, 1800 g of iron phosphate, 743.5 g of lithium carbonate, 257.3 g of sucrose, and 128.6 g of polyethylene glycol were weighed, mixed in 7 kg of pure water, and placed in a sand mill for thorough sand grinding. The sand-milled slurry was spray-dried to obtain a dry material 1;

[0073] (2) placing the dried material 1 obtained in step (1) in a box-type atmosphere furnace, and sintering at 520° C. for 5 h in a mixed atmosphere of circulating nitrogen (99%) and ethane (1%) to obtain a sintered material 1;

[0074] (3) Weigh 2000 g of the sintered material 1 obtained in step (2), add 10 g of polyethylene glycol and 8 g of Super P, mix in 4 kg of pure water, and place in a sand mill for thorough sand grinding. Spray dry the sand milled slurry to obtain a dried material 2;

[0075] (4) The dried material 2 obtained in step (3) is placed in a box-type atmosphere furnace, and sintered at 740° C. for 4 h in a circulating nitrogen atmosphere to obtain a sintered material 2, which is then mechanically crushed to obtain lithium manganese iron phosphate.

[0076] Example 3

[0077] The method for preparing lithium manganese iron phosphate provided in this embodiment comprises the following steps:

[0078] (1) 751.9 g of manganese dioxide, 2000 g of iron phosphate, 1015.2 g of monoammonium phosphate, 824.8 g of lithium carbonate, 68.9 g of glucose, 68.8 g of fructose, and 367.4 g of polyvinyl pyrrolidone were weighed, mixed in 8 kg of pure water, and placed in a sand mill for thorough sand grinding. The sand-milled slurry was spray-dried to obtain a dry material 1;

[0079] (2) placing the dried material 1 obtained in step (1) in a box-type atmosphere furnace, and sintering at 450° C. for 8 h in a mixed atmosphere of circulating nitrogen (99%) and propane (1%) to obtain a sintered material 1;

[0080] (3) Weigh 2000 g of the sintered material 1 obtained in step (2), add 60 g of polyvinyl pyrrolidone and 4 g of Ketjen black, mix in 4 kg of pure water, and place in a sand mill for thorough sand grinding. Spray dry the sand-milled slurry to obtain a dried material 2;

[0081] (4) The dried material 2 obtained in step (3) is placed in a box-type atmosphere furnace, and sintered at 700° C. for 2 h in a circulating nitrogen atmosphere to obtain a sintered material 2, which is then mechanically crushed to obtain lithium manganese iron phosphate.

[0082] Example 4

[0083] The method for preparing lithium manganese iron phosphate provided in this embodiment comprises the following steps:

[0084] (1) Weigh 751.9 g of manganese dioxide, 2000 g of iron phosphate, 1015.2 g of monoammonium phosphate, 824.8 g of lithium carbonate, 229.6 g of galactose, 229.5 g of maltose, and 275.5 g of ascorbic acid, mix them in 8 kg of pure water, and place them in a sand mill for thorough sand grinding. The sand milled slurry is spray dried to obtain a dried material 1;

[0085] (2) placing the dried material 1 obtained in step (1) in a box-type atmosphere furnace, and sintering at 550° C. for 5 h in a mixed atmosphere of circulating nitrogen (99%) and methane (1%) to obtain a sintered material 1;

[0086] (3) Weigh 2000 g of the sintered material 1 obtained in step (2), add 40 g of ascorbic acid and 14 g of graphene oxide, mix in 4 kg of pure water, and place in a sand mill for thorough sand grinding. Spray dry the sand milled slurry to obtain a dried material 2;

[0087] (4) The dried material 2 obtained in step (3) is placed in a box-type atmosphere furnace, and sintered at 800° C. for 5 h in a circulating nitrogen atmosphere to obtain a sintered material 2, which is then mechanically crushed to obtain lithium manganese iron phosphate.

[0088] Example 5

[0089] The method for preparing lithium manganese iron phosphate provided in this embodiment comprises the following steps:

[0090] (1) 751.9 g of manganese dioxide, 2000 g of iron phosphate, 1015.2 g of monoammonium phosphate, 824.8 g of lithium carbonate, 76.5 g of fructose, 76.4 g of galactose, 74.6 g of sucrose, and 183.7 g of citric acid were weighed, mixed in 8 kg of pure water, and placed in a sand mill for thorough sand grinding. The sand-milled slurry was spray-dried to obtain a dry material 1;

[0091] (2) placing the dried material 1 obtained in step (1) in a box-type atmosphere furnace, and sintering at 600° C. for 4 h in a mixed atmosphere of circulating nitrogen (99%) and acetylene (1%) to obtain a sintered material 1;

[0092] (3) Weigh 2000 g of the sintered material 1 obtained in step (2), add 20 g of citric acid and 20 g of carbon nanotubes, mix in 4 kg of pure water, and place in a sand mill for thorough sand grinding. Spray dry the sand milled slurry to obtain a dried material 2;

[0093] (4) The dried material 2 obtained in step (3) is placed in a box-type atmosphere furnace, and sintered at 780° C. for 5 h in a circulating nitrogen atmosphere to obtain a sintered material 2, which is then mechanically crushed to obtain lithium manganese iron phosphate.

[0094] Comparative Example 1

[0095] The only difference between this comparative example and Example 1 is that in step (1), 475.6 g of sucrose is used instead of the first composite carbon source.

[0096] Comparative Example 2

[0097] The only difference between this comparative example and Example 1 is that in step (2), sintering is carried out under a pure nitrogen atmosphere.

[0098] Comparative Example 3

[0099] The only difference between this comparative example and Example 1 is that 20 g of acetylene black is used in step (3) to replace the second composite carbon source.

[0100] Comparative Example 4

[0101] The difference between this comparative example and Example 1 is that the amount of sucrose added in step (1) is 45.91 g, and the amount of polyethylene glycol added is 459.1 g.

[0102] Comparative Example 5

[0103] The only difference between this comparative example and Example 1 is that the amount of polyethylene glycol added in step (3) is 2 g, and the amount of acetylene black added is 40 g.

[0104] Comparative Example 6

[0105] The only difference between this comparative example and Example 1 is that the sintering temperature in step (2) is 650°C.

[0106] Comparative Example 7

[0107] The only difference between this comparative example and Example 1 is that the sintering temperature in step (4) is 650°C.

[0108] Experimental example

[0109] The performance of the lithium iron manganese phosphate prepared in each embodiment and comparative example was tested, and the testing method was as follows: 1) Powder resistivity: a four-probe powder resistivity tester was used, and the test object was set to a cylindrical material with a diameter of 20 mm; the test mode was set to square resistance, and the linear probe spacing was 2 mm; 1 g of lithium iron manganese phosphate powder was filled in the mold, the pressure was set to 800 kg, the constant pressure was maintained for 30 seconds, and the instrument measurement results were recorded; 2) Electrical properties: the prepared lithium iron manganese phosphate was used as the positive electrode active material, and the active material, conductive agent (Super-P), and binder (PVDF) were added in a ratio of 9:0.5:0.5 and uniformly dispersed in N-methylpyrrolidone (NMP) to obtain an electrode slurry, which was coated on an aluminum foil, and sliced ​​to obtain a positive electrode sheet after vacuum drying at 100°C for 12 hours. Using argon as the protective gas, the positive electrode sheet, the negative electrode sheet (metal lithium), the separator (U.S. Celgard2325) and the electrolyte (1M LiPF6 ethylene carbonate / diethyl carbonate solution, volume ratio 1:1) were assembled into a CR2032 button battery in a glove box. The charging and discharging performance of the battery was tested using the Blue Electric test system: constant current and constant voltage charging (cut-off voltage 3.75V, cut-off current 20mA), constant current discharge (cut-off voltage 2.0V). The test results are shown in Table 1.

[0110] Table 1 Performance test results of lithium manganese iron phosphate

[0111]

[0112] It can be seen from Table 1 that the method for preparing lithium manganese iron phosphate provided by the present invention can reduce the resistivity of the lithium manganese iron phosphate prepared and improve the electrochemical performance.

[0113] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for preparing lithium manganese iron phosphate, characterized in that: The following steps are involved: (a) subjecting a mixed solution containing an iron source, a manganese source, a lithium source, a phosphorus source and a first composite carbon source to a first sand milling and a first drying to obtain a dried material; (b) subjecting the dried material to a first sintering in a composite atmosphere to obtain a sintered material; (c) subjecting the mixed solution containing the sintering material and the second composite carbon source to a second sand milling, a second drying and a second sintering.

2. The method for preparing lithium iron manganese phosphate according to claim 1, characterized in that: The first composite carbon source comprises: a first carbon source and a second carbon source; And / or, the second composite carbon source includes: a third carbon source and a fourth carbon source.

3. The method for preparing lithium manganese iron phosphate according to claim 2, characterized in that: The first carbon source comprises: at least one of glucose, fructose, galactose, sucrose or maltose; And / or, the second carbon source includes: at least one of polyethylene glycol, polyvinyl pyrrolidone, ascorbic acid or citric acid.

4. The method for preparing lithium iron manganese phosphate according to claim 2, characterized in that: The mass of the first carbon source is 3% to 10% of the total mass of the iron source, the manganese source, the lithium source and the phosphorus source; And / or, the mass of the second carbon source is 2% to 8% of the total mass of the iron source, the manganese source, the lithium source and the phosphorus source.

5. The method for preparing lithium manganese iron phosphate according to claim 2, characterized in that: The third carbon source comprises: at least one of polyethylene glycol, polyvinyl pyrrolidone, ascorbic acid or citric acid; And / or, the fourth carbon source includes at least one of Super P, acetylene black, Ketjen black, graphene oxide or carbon nanotubes.

6. The method for preparing lithium manganese iron phosphate according to claim 2, characterized in that: The mass of the third carbon source is 0.5% to 3% of the mass of the sintering material; And / or, the mass of the fourth carbon source is 0.2% to 1% of the mass of the sintering material.

7. The method for preparing lithium manganese iron phosphate according to claim 1, characterized in that: The composite atmosphere includes: an inert atmosphere and a reducing atmosphere; Preferably, the reducing atmosphere comprises: at least one of methane, ethane, acetylene or propane; Preferably, the reducing atmosphere content does not exceed 2% of the total volume of the composite atmosphere.

8. The method for preparing lithium manganese iron phosphate according to claim 1, characterized in that: Includes at least one of the following technical features: (1) The temperature of the first sintering is 450-600° C.; (2) The first sintering time is 4 to 8 hours; (3) The temperature of the second sintering is 700-800° C.; (4) The second sintering time is 2 to 6 hours.

9. A positive electrode sheet, characterized in that: The lithium manganese phosphate is mainly prepared by the lithium manganese phosphate preparation method according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Preparation method of lithium manganese iron phosphate positive electrode material and lithium manganese iron phosphate positive electrode material

    CN120288731A